Molecular analysis of the reactions in Salicornia europaea to varying NaCl concentrations at various stages of development to better exploit its potential as a new crop plant - Fussy, Andre; Papenbrock, Jutta (Frontiers in Plant Science, 2024)
Freshwater scarcity demands exploration of alternative resources like saline water and soils. Understanding the molecular mechanisms behind NaCl regulation in potential crop plants becomes increasingly important for promoting saline agriculture. This study investigated the euhalophyte Salicornia europaea, analyzing its gene expression, yield, and total phenolic compounds under hydroponic cultivation. We employed five salinity levels (0, 7.5, 15, 22.5, and 30 g/L NaCl) across five harvests at 15-day intervals, capturing plant development. Notably, this design deviated from conventional gene expression studies by recording organ-specific responses (shoots and roots) in plants adapted to long-term salinity treatments at various developmental stages. The highest fresh mass of S. europaea was observed four months after germination in 15 g/L NaCl. Identifying a reliable set of reference genes for normalizing gene expression data was crucial due to comparisons across shoots, roots, developmental stages, and salinity levels. A set of housekeeping genes – ubiquitin c (SeUBC), actin (SeActin) and dnaJ-like protein (SeDNAJ) – was identified for this purpose. Interestingly, plants grown without NaCl (0 g/L) displayed upregulation of certain genes associated with a NaCl deficiency related nutritional deprivation. These genes encode a tonoplast Na+/H+-antiporter (SeNHX1), a vacuolar H+-ATPase (SeVHA-A), two H+-PPases (SeVP1, SeVP2), a hkt1-like transporter (SeHKT), a vinorine synthase (SeVinS), a peroxidase (SePerox), and a plasma membrane Na+/H+-antiporter (SeSOS1). Other genes encoding an amino acid permease (SeAAP) and a proline transporter (SeProT) demonstrated marginal or dispersing salinity influence, suggesting their nuanced regulation during plants development. Notably, osmoregulatory genes (SeOsmP, SeProT) were upregulated in mature plants, highlighting their role in salinity adaptation. This study reveals distinct regulatory mechanisms in S. europaea for coping with varying salinity levels. Identifying and understanding physiological reactions and sodium responsive key genes further elucidate the relationship between sodium tolerance and the obligate sodium requirement as a nutrient in euhalophytes.